A new approach to hyper dual numbers with tribonacci and tribonacci-Lucas numbers and their generalized summation formulas - Ahmad Ali Mehrad; Mansoor Kakar Mirwais (Journal of Innovative Applied Mathematics and Computational Sciences)
Motivated by the definition of Tribonacci quaternions, we define hyper-dual numbers whose components involve Tribonacci and Tribonacci-Lucas numbers. We refer to these new numbers as hyper-dual Tribonacci numbers and hyper-dual Tribonacci-Lucas numbers, respectively.